Boosting Amination of 1‐Octanol to 1‐Octylamine via Metal‐Metal Oxide Interactions in NixFe1/Al2O3 Catalysts. Issue 7 (10th February 2022) - Wang, Shiqing; Lan, Xiaocheng; Liu, Boyang; Ali, Babar; Wang, Tiefeng
Abstract: The synthesis of 1‐octylamine, a primary platform molecule, remained a great challenge in catalysis. In this work, Ni x Fe1 /Al2 O3 was used for direct amination of 1‐octanol to 1‐octylamine. Catalyst evaluation indicated that the promotion effect of Fe/Ni ratio on the catalytic amination activity followed a volcano curve while the selectivity to 1‐octylamine was positively correlated with the Fe loading. Compared with the Ni/Al2 O3 catalyst, the amination activity was increased by 2.8 times by optimizing the Fe/Ni ratio to 0.33, and the selectivity to 1‐octylamine was increased from 84.0 % to 96.3 % when increasing the Fe/Ni ratio from 0 to 1. Based on catalyst characterizations, the good performance of Ni x Fe1 /Al2 O3 was ascribed to the combined modification effect of the NiFe alloy and Ni−FeO x interface. The FeO x species enriched on the Ni particle surface provided sufficient Fe 2+ /Fe 3+ −O 2− sites for the activation of 1‐octanol, and the cooperation between Ni sites and Lewis acid‐base pairs enhanced the amination of 1‐octanol to 1‐octylamine. This work sheds new light on the design of Ni‐based catalysts without using a noble metal for primary amine preparation. Abstract : Octylamine synthesis : Ni x Fe1 /Al2 O3 was used as catalyst for 1‐octanol amination and provided the highest yield among the reported nonprecious metal catalysts. The generation of Ni−FeO x interactions provided sufficient Fe 2+ /Fe 3+ −O 2− sites for the activation of 1‐octanol. Meanwhile, the cooperation between Ni site and Lewis acid‐base pairs significantly enhanced the amination of 1‐octanol to 1‐octylamine.